Perbedaan Prestasi Belajar Ditinjau Berdasarkan Pola Asuh Orangtua - Cynthia Florencia; Agoes Dariyo; Debora Basaria (Psibernetika, 2017)
Education has always been one of the basic necessities of any individual’s life. Education provides opportunities for children to learn, prepare for the future, and be able to change the lives of present and future generations. With education, people can obtain academic achievements that will be useful for his life. Academic achievement in adolescents can be influenced by parenting styles. The aim of the current study is to examine the differences in academic achievement in adolescents based on parenting styles. This study utilizes quantitative data and has 386 subjects.  Data were retrieved through parenting styles questionnaires as well as grade point average (GPA). Data is processed by using One Way ANOVA. Based on the results of research, it was found that there was no differences in academic achievement in adolescents based on parenting, either by father or mother, with a p score on father parenting = .223 and the p score on mother parenting = .737.Keywords: academic achievement, parenting styles, adolescence